One-step chronoamperometric synthesis of S, N co-doped graphene oxide electrodes for nonenzymatic electrochemical H2O2 sensor - Kocyigit, Nilufer; Zor, Sule Dinc; Yagci, Ozlem; Arvas, Melih Besir (SPRINGER, 2024)
In this study, an S, N-codoped graphene oxide electrode was synthesised by a one-step chronoamperometric method to modify a pencil graphite electrode (PGE) for the non-enzymatic detection of H2O2. The electrochemical characterisation of modified PGE was carried out by means of cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). The morphology and structural properties of this electrode was investigated by FTIR, XPS, XRD, Raman and SEM analysis. The S, N-codoped graphene oxide electrode has a high sensitivity with linear range of 0.1-90 mu M with correlation coefficient (R2 = 0.9959) and a low detection limit with a concentration of 0.015 mu Mf. Real sample analyses of the sensor, whose efficiency was investigated for practical application, were performed on real sample. The novelty of this study compared to the literature is the use of S,N Co-doped GO electrode synthesised in a single step as a nonenzymatic sensor for H2O2, achieving high sensitivity and low detection limit. Furthermore, this study presents the production of graphene oxide electrodes co-doped with sulfur and nitrogen in a single step, utilising the chronoamperometry method, which is a rapid, straightforward, and cost-effective process. Concurrently, the formation of graphene layers on the PGE surface was ensured, while oxygenated functional groups containing sulfur and nitrogen were incorporated into the structure. The determination of H2O2 was conducted without the use of enzymes with the S,N co-doped GO electrode, which exhibits high stability and does not necessitate an additional purification and separation step. On the basis of obtained results, the S, N-codoped graphene oxide electrode exhibited good performance such as satisfying accuracy for H2O2 detection in the pharmaceutical sample with excellent reproducibility and stability.
Keywords: HYDROGEN-PEROXIDE; EFFICIENT ELECTROCATALYST; NITROGEN; SULFUR; NANOPARTICLES; PERFORMANCE; SUPERCAPACITOR; FABRICATION; SHEETS; GREEN; Engineering; Materials Science; Physics